Candidate feedback on the Induction and Refresher (I&R) scheme-simulated surgery. Issue 4 (4th July 2019) - Khan, Anwar; Nayar, Vijay; Burrows, Peter; Muthuswamy, Radha
ABSTRACT: The simulated surgery examination is one of the tripos of entry assessments for the Induction and Refresher (I&R) Scheme. It is used to assess the clinical and consulting skills of GPs prior to a period of supervised practice. The assessment involves observing candidates consulting with simulated patients played by role-players presenting standardised cases. Additionally, this assessment provides an 'educational prescription' for both passing and failing candidates as well as evidence of linguistic competency for overseas candidates. A feedback questionnaire is administered to candidates immediately after the examination, to seek their views and to evaluate their experience of the exam. Between July 2015 and July 2018, 401 candidates completed the examination and questionnaire. Quantitative and qualitative data has been collected and analysed with the findings reported in this paper. Overall candidates are satisfied with the examination, and regard it as a valid assessment of their GP consulting skills. However, there are still concerns regarding the I&R application process although there is evidence that there has been a trajectory of improvement over the past three years. Candidate feedback obtained has been used in an iterative manner to ensure quality control of the examination as well as for prompting improvements in the process.